Reforming Village-Level Governance via Horizontal Pressure : Evidence from an Experiment in Zimbabwe - Baldwin, Kate; Muyengwa, Shylock; Mvukiyehe, Eric (World Bank, Washington, DC, 2017)
How can patrimonial local-level governance be reformed? Debates on this topic have focused largely on the possibility of reform via pressure from above (superordinate leaders) or below (citizens). This paper tests whether horizontal pressures from civil society leaders can reform local governance in a context where neither of these mechanisms operates effectively. The study analyzes an experimental intervention in Zimbabwe intended to reduce abuse of power by village heads. Analytic leverage comes from the fact that the 270 study villages were randomly assigned to two variants of the intervention, one in which only village heads were trained on the framework governing village leadership, and one in which civil society leaders were trained alongside village heads. The results suggest that horizontal pressure from civil society leaders increased village heads' knowledge of and compliance with regulated procedures, improved their management of issues and raised citizens' trust in their leadership. A quantitative and qualitative analysis of the mechanisms through which the trained civil society leaders had these effects suggests they accomplished reform by directly applying social pressure on village heads to abide by regulations.